Shibli Nu’mani’s Contribution to Revitalization of ‘Ilm al-Kala > m - Fejri Gasman (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2013)
The present research is an attempt to explicate Shibli> Nu’ma>ni>’scontribution of ‘ilm al-Kala > m which to Muslim is a pivotal matter in terms ofboth its doctrine and practice. This study attempts at examining Shibli> Nu’ma>ni>’sviews in dealing with religious problems in his community, and how hepropagated his ideas in revitalization of ‘ilm al-Kala > m. It seeks to discover severalaspects of Shibli> Nu’ma>ni>’s thoughts of ‘ilm al-Kala > m, such as the coherentrelationship of religion and science, Islamic culture, Islamic legal system, Islamiceducational system, Islamic political science, reason and revelation, prophecy,and tawh i > d. This study concludes that Shibli> Nu’ma>ni>’s understanding of ‘ilm-al-Kala > m is in line with the teaching of ahl al-sunnah wa al-jama > ’ah, and he was verymuch influenced by Ima>m al-Ghaza>li>’s and Jala>l al-Din Ru>mi>’s thoughts. Healso succeeded in harmonizing traditional and modern system of thoughts aswell as synthesizing the theologian’s approach with the s u > fi > tradition